PERIODIZATION REGULATORY FRAMEWORK REGULATION OF LAND RELATIONS LOCAL GOVERNMENT IN UKRAINE - Bisikin S.V. (Pressing Problems of Public Administration, 2015)
The article singles out and systematized during the formation of the legal framework regulating land relations local authorities in Ukraine, the role of this process in local government.